2009
DOI: 10.1007/s00436-009-1670-z
|View full text |Cite
|
Sign up to set email alerts
|

A nested PCR assay exhibits enhanced sensitivity for detection of Theileria parva infections in bovine blood samples from carrier animals

Abstract: Theileria parva causes East Coast fever, an economically important disease of cattle in sub-Saharan Africa. We describe a nested polymerase chain reaction (nPCR) assay for the detection of T. parva DNA in cattle blood spotted onto filter paper using primers derived from the T. parva-specific 104-kDa antigen (p104) gene. The sensitivity of this assay was compared to a previously described p104-based PCR and also the reverse line blot (RLB) technique, using serial dilutions of blood from a calf with known T. par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…The present study is in agreement with Rady et al (2010) and Odongo et al (2010). Altay et al (2005), Durrani et al (2008), Azizi et al (2008), Bami et al (2009) also reported that PCR was more sensitive than the traditional method of blood smear examination who also used the same primers for detection of Theileria organisms in blood.…”
Section: Resultssupporting
confidence: 92%
“…The present study is in agreement with Rady et al (2010) and Odongo et al (2010). Altay et al (2005), Durrani et al (2008), Azizi et al (2008), Bami et al (2009) also reported that PCR was more sensitive than the traditional method of blood smear examination who also used the same primers for detection of Theileria organisms in blood.…”
Section: Resultssupporting
confidence: 92%
“…This included conventional PCR followed by agarose gel electrophoretic analysis (Bishop et al., 1992; Pienaar et al., 2011a), PCR-RFLP methods (Bishop et al., 1992; Geysen et al., 1999; Heidarpour Bami et al., 2009; Zaeemi et al., 2011), nested-PCR (Odongo et al., 2010), PCR followed by dot blotting, capillary blotting or slot-blotting and hybridisation using radio-isotope labelled probes (Bishop et al., 1992; Allsopp et al., 1993; Collins et al., 2002; Skilton et al., 2002). The latter was improved by the non-radio-active reverse line blot method that used chemiluminescence (Gubbels et al., 1999; Schnittger et al., 2004), with recent variation on this technique using a DNA bead-based suspension array (Ros-García et al., 2012a, 2013).…”
Section: Diagnosticsmentioning
confidence: 99%
“…In contrast, the Marikebuni strain maintained the carrier-state indefinitely well above the LOD (Bishop et al., 1992; Skilton et al., 2002). Prevalence of T. parva in cattle from East Coast fever endemic regions range between 37 and 42% using nested PCR (Odongo et al., 2010), compared to ~80% in buffalo (Pienaar et al., 2011a), suggesting that the former is not compatible with an endemic stable situation. In East Coast fever, the carrier-state may therefore be strain dependent and intermittent.…”
Section: Sensitivity Of Molecular Assays Carrier State and Parasitaementioning
confidence: 99%
“…DNA was extracted using the DNeasy Blood and Tissue kit (Qiagen, Hilden, Germany) according to instructions. The p104 gene PCR parameters and the primers used in the primary PCR were as described previously [25, 26]. All reactions were performed in 15 μl volumes using 5 μl of DNA extracted from blood for the primary reaction or 5 μl of the primary PCR reaction for the nested PCR reaction with 0.25 units of Taq DNA polymerase, (Promega, Madison, USA), 1× PCR buffer (Promega), 200 mM of each dNTP (Promega) and 25 ng of primers and 1.5 mM of MgCl 2 .…”
Section: Methodsmentioning
confidence: 99%